(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Urinary tract endometriosis (UTE) is the presence of endometriotic implants in the bladder, ureter, kidneys, or urethra. It affects 1% of women with endometriosis and occurs more commonly among those with deep infiltrative endometriosis. Bladder endometriosis is the most common presentation, comprising 85% of cases. Concomitant involvement of the bladder and ureter is rare, comprising 1.4% of all cases. The clinical presentation involves lower urinary tract symptoms, that worsen during menses. Timely diagnosis and treatment are crucial in ameliorating symptoms and preventing complications, such as obstructive nephropathy. This is a case of bladder endometriosis with ureteral involvement, outlining management challenges, reviewing evidence on management approaches, and highlighting the experience gained from this case in managing complex UTE. Case presentation: A 38-year-old female presented with a longstanding history of pelvic pain, dysuria, and new-onset voiding difficulty. She had undergone two prior surgical procedures for endometriosis, including a total abdominal hysterectomy. Her physical examination was normal. Ultrasound revealed a 3-cm intracavitary bladder mass, which was described as likely endometriosis on magnetic resonance imaging. On cystoscopy the mass was noted to be larger, encasing the left ureteric meatus. A laparoscopic cystostomy was performed, with partial resection of the mass and placement of a temporary ureteric stent. After three months of medical treatment with dienogest, cystoscopy revealed a significant reduction in size with sub-centimeter residual avascular tissue. This was resected avoiding the ureter and ureteric meatus. A new ureteric stent was placed. A repeat cystoscopy three months later revealed good healing with no residual endometriosis. The stent was removed, and a retrograde pyelogram confirmed no meatal stenosis or ureteric obstruction. She has remained symptom-free. Conclusion: Medical and surgical options are available for bladder endometriosis, with partial cystectomy being the gold standard. The initial approach is dependent on the size of the lesion and the extent of ureteric involvement. A staged approach that combines medical or surgical management can ensure optimal outcomes while reducing surgery-associated morbidity in complex cases.